2012
DOI: 10.1111/jgs.12038
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden in Chronically Ill Homebound Individuals

Abstract: Objectives To document the degree of symptom burden in an urban homebound population. Design Cross-sectional survey. Setting The Mount Sinai Visiting Doctors Program (MSVD). Participants All individuals newly enrolled in the MSVD. Measurements Edmonton Symptom Assessment Scale (ESAS), which consists of 10 visual analogue scales scored from 0 to 10; symptoms include pain, tiredness, nausea, depression, anxiety, drowsiness, appetite, well-being, shortness of breath, and other. Results ESAS scores were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 36 publications
(62 reference statements)
2
63
0
1
Order By: Relevance
“…Older people with advanced chronic diseases are known to suffer from symptoms such as pain, lack of energy/fatigue, shortness of breath and loss of appetite (Walke et al 2006, Wajnberg et al 2013). However, the way a symptom is perceived is a unique experience and a lack of symptom control may result in significant deterioration of health-related quality of life (Newcomb 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Older people with advanced chronic diseases are known to suffer from symptoms such as pain, lack of energy/fatigue, shortness of breath and loss of appetite (Walke et al 2006, Wajnberg et al 2013). However, the way a symptom is perceived is a unique experience and a lack of symptom control may result in significant deterioration of health-related quality of life (Newcomb 2010).…”
Section: Introductionmentioning
confidence: 99%
“…8 Similarly, hospice patients in various settings, including the home, experienced severe symptom burden such as lack of energy (83%), pain (76%), and loss of appetite (63%). 9 Although studies have examined interventions that have decreased pain over time in patients with conditions such as arthritis and cancer, 10 few studies have evaluated symptom control over time for patients in diverse long-term settings.…”
mentioning
confidence: 99%
“…We focused on three symptoms that our previous research found were most prevalent (approximately 50%) for homebound patients at enrollment in HBPC-pain, tiredness, and loss of appetite. 8 We also included depression and anxiety as they substantially impact patient quality of life, 17,18 disability, 19 and health care costs, [20][21][22] and they may be particularly amenable to in-home intervention through primary care or specialist referral.…”
mentioning
confidence: 99%
“…60,61 The most relevant aspects of palliative care medicine for complex geriatric patients are quality-of-life assessment, symptom management, advance care planning, and attention to family experiences in care. 62 Providing support for caregivers in the form of respite care also is an important feature of high-performing geriatric models of care.…”
Section: Features Of Complex Care Delivery Models That Provide Value mentioning
confidence: 99%